Aplikasi Pendaftaran Pelatihan di Dinas Perindustrian Kota Medan Berbasis Android - Anri Hafiz Tua; M. Iqbal Natama Harahap; Rizki Abdul Hakim Siregar (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to optimize training registration in the Medan City Industry Service through an android-based application. The benefits of this research are to save people's time and energy and reduce the workload of the Medan City Industry Office staff, because registration is done online through RED APPEL. The application is designed using Java programming on Android Studio, MySQL system management database on XAMPP software. The results of the research are training registration, taking training materials through APPEL MERAH (Medan Berkah Training Application) without having to come to the Medan City Industry Office. This application is very important among people who want to take part in training at the Medan City Industry Office because it can be accessed via their respective Smartphones.